Komunikowanie międzykulturowe. Przypomnienie głównych tez - Golka, Marian (Zakład Pedagogiki Społecznej Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
Intercultural communication is common, although different is the degree of cultural differences between partners in communications. Every act of communication requires a certain portion of common cultural competence that is the ability to understand symbolic messages. Each act of of intercultural communication is also a kind of "translation", as it involves a "translation" from a different culture to one's own culture. This is possible thanks to a certain similarity of cultures and a will to communicate.
Keywords: interaction; multiculturalism; agreement; understanding; interpretation